Mutation burden analysis of six common mental disorders in African Americans by whole genome sequencing. Issue 22 (1st June 2022) - Liu, Yichuan; Qu, Hui-Qi; Chang, Xiao; Qu, Jingchun; Mentch, Frank D; Nguyen, Kenny; Tian, Lifeng; Glessner, Joseph; Sleiman, Patrick M A; Hakonarson, Hakon
Abstract: Mental disorders present a global health concern and have limited treatment options. In today's medical practice, medications such as antidepressants are prescribed not only for depression but also for conditions such as anxiety and attention deficit hyperactivity disorder (ADHD). Therefore, identifying gene targets for specific disorders is important and offers improved precision. In this study, we performed a genetic analysis of six common mental disorders—ADHD, anxiety, depression, delays in mental development, intellectual disabilities (IDs) and speech/language disorder—in the ethnic minority of African Americans (AAs) using whole genome sequencing (WGS). WGS data were generated from blood-derived DNA from 4178 AA individuals, including 1384 patients with the diagnosis of at least one mental disorder. Mutation burden analysis was applied based on rare and deleterious mutations in the AA population between cases and controls, and further analyzed in the context of patients with single mental disorder diagnosis. Certain genes uncovered demonstrated significant P- values in mutation burden analysis. In addition, exclusive recurrences in specific type of disorder were scanned through gene–drug interaction databases to assess for availability of potential medications. We uncovered 15 genes harboring deleterious mutations, including 3-Hydroxy-3-Methylglutaryl-CoA Reductase ( HMGCR ) and Uronyl 2-Sulfotransferase ( UST ) for ADHD; Farnesyltransferase, CAAX Box, Beta ( FNTB ) for anxiety; Xin Actin Binding Repeat Containing 2 ( XIRP2 ), Natriuretic Peptide C ( NPPC ), Serine/Threonine Kinase 33 ( STK33 ), Pannexin 1 ( PANX1 ) and Neurotensin ( NTS ) for depression; RUNX Family Transcription Factor 3 ( RUNX3 ), Tachykinin Receptor 1 ( TACR1 ) and NADH:Ubiquinone Oxidoreductase Core Subunit S7 ( NDUFS7 ) for delays in mental development; Hepsin ( HPN ) for ID and Collagen Type VI Alpha 3 Chain ( COL6A3 ), Damage Specific DNA Binding Protein 1 ( DDB1 ) and NADH:Ubiquinone Oxidoreductase Subunit A11 ( NDUFA11 ) for speech/language disorder. Taken together, we have established critical insights into the development of new precision medicine approaches for mental disorders in AAs.